2010
DOI: 10.1002/per.741
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and unmitigated communion in support providers

Abstract: In this research, we argue and demonstrate that the association between enacted (un)supportive behaviour and depressive symptoms is a function of the providers' levels of unmitigated communion (UC). UC is characterized by overinvolvement in others' problems, self-neglect and externalized self-evaluation. These characteristics appear to predispose individuals high in UC to experience depressive symptoms. As anticipated, we show that enacted supportive behaviour was negatively associated with depressive symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
4
1
Order By: Relevance
“…For these individuals, providing support may have been more taxing, or they may have been aware that their behaviors were ineffective. These findings are in contrast to two previous studies showing that low rather than high unmitigated communion individuals reaped the benefits of support provision (Helgeson et al, 2015; Jin et al, 2010). However, neither of those studies focused on a patient population in which support needs are higher and the consequences of support more critical.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For these individuals, providing support may have been more taxing, or they may have been aware that their behaviors were ineffective. These findings are in contrast to two previous studies showing that low rather than high unmitigated communion individuals reaped the benefits of support provision (Helgeson et al, 2015; Jin et al, 2010). However, neither of those studies focused on a patient population in which support needs are higher and the consequences of support more critical.…”
Section: Discussioncontrasting
confidence: 99%
“…Unmitigated communion also may have implications for the health of the support provider—the partner. In a cross-sectional study of healthy college students (Jin, Van Yperen, Sanderman, & Hagedoorn, 2010) and a daily diary study of healthy college students (Helgeson et al, 2015), unmitigated communion moderated the relation of support provision to health. Both studies showed that people who scored low on unmitigated communion benefited from being able to provide support but those who scored high on unmitigated communion did not.…”
Section: Interactions With Personalitymentioning
confidence: 99%
“…In this regard, occupational communion may be a central process that influences the nature of social support processes and interactions. For example, people who are depressed and who also pose a highly communal orientation to social relationships do not derive pleasure or a sense of achievement from their support provisions or caring role (Jin et al ., 2010). Future quantitative research could explore whether occupational communion mediates the quality of the care or support workers provide people with dementia and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Unmitigated agency (focus on oneself and exclusion of others) would lead to physiological reactivity and should manifest in biological measures [33]. Unmitigated communion (focus on others and neglect of oneself) would enforce psychological distress, which should become evident in subjective health ratings [34]. This is especially interesting regarding our study focusing effects on subjective and biological stress measures.…”
Section: Gender-role Orientationmentioning
confidence: 87%